A Nanomechanical Investigation of Engineered Bone Tissue Comparing Elastoplastic and Viscoelastoplastic Modeling - Marco Boi; Gregorio Marchiori; Maria Sartori; Francesca Salamanna; Gabriela Graziani; Alessandro Russo; Andrea Visani; Mauro Girolami; Milena Fini; Michele Bianchi (Advances in Materials Science and Engineering)
It is common practice to implement the elastoplastic Oliver and Pharr (OP) model to investigate the spatial and temporal variations of mechanical properties of engineered bone. However, the viscoelastoplastic (VEP) model may be preferred being envisaged to provide additional insights into the regeneration process, as it allows evaluating also the viscous content of bone tissue. In this work, the elastic modulus (ER), contact hardness (HC), hardness (H), and viscosity index (ηQ) of newly formed bone tissue regenerated at 4 and 12 weeks from the implantation of a macroporous hydroxyapatite scaffold in a rabbit femoral critical-size model were addressed and compared to the mechanical properties of preexisting bone. Indentation curves were fitted with both the OP and VEP models. The VEP model outlined a wider gap between the mechanical properties of native and regenerated tissue when compared to the OP model. In addition, the VEP model indicated an increase of the viscosity index from 4 to 12 weeks, supporting the evidence of a still active regeneration process. The reported results confirmed the higher ability of VEP model compared to the more diffused OP model to provide important insights into bone mechanical properties, also during the bone regeneration process.